Comment on Jukema et al. (2015), "Geographic variation in morphometrics, molt, and migration suggests ongoing subspeciation in Pacific Golden-Plovers (Pluvialis fulva)". (20th January 2016) - Cibois, Alice; Sheldon, Frederick H.
Abstract: Jukema and colleagues published in The Auk a study dealing with geographic variation within the Pacific Golden-Plover ( Pluvialis fulva ). We highlight a taxonomic problem created unwittingly by the last sentence of their article, in which the authors suggest a new name for the Siberian population.